Brain endothelial dysfunction in cerebral adrenoleukodystrophy. (16th September 2015) - Musolino, Patricia L.; Gong, Yi; Snyder, Juliet M. T.; Jimenez, Sandra; Lok, Josephine; Lo, Eng H.; Moser, Ann B.; Grabowski, Eric F.; Frosch, Matthew P.; Eichler, Florian S.
Abstract : See Aubourg (doi:10.1093/awv271 ) for a scientific commentary on this article. Cerebral adrenoleukodystrophy is a neuroinflammatory demyelinating disease caused by mutations in ABCD1 . Musolino et al . report that the progressive demyelination coincides with blood-brain barrier disruption and endothelial changes. Silencing endothelial ABCD1 in vitro upregulates expression of adhesion molecules and downregulates expression of tight-junction proteins and c-MYC, promoting monocyte transmigration. Abstract : Abstract : See Aubourg (doi:10.1093/awv271 ) for a scientific commentary on this article. X-linked adrenoleukodystrophy is caused by mutations in the ABCD1 gene leading to accumulation of very long chain fatty acids. Its most severe neurological manifestation is cerebral adrenoleukodystrophy. Here we demonstrate that progressive inflammatory demyelination in cerebral adrenoleukodystrophy coincides with blood–brain barrier dysfunction, increased MMP9 expression, and changes in endothelial tight junction proteins as well as adhesion molecules. ABCD1, but not its closest homologue ABCD2, is highly expressed in human brain microvascular endothelial cells, far exceeding its expression in the systemic vasculature. Silencing of ABCD1 in human brain microvascular endothelial cells causes accumulation of very long chain fatty acids, but much later than the immediate upregulation of adhesion molecules and decrease in tight junction proteins. This results in greater adhesion and transmigration of monocytes across the endothelium. PCR-array screening of human brain microvascular endothelial cells after ABCD1 silencing revealed downregulation of both mRNA and protein levels of the transcription factor c-MYC (encoded by MYC ). Interestingly, MYC silencing mimicked the effects of ABCD1 silencing on CLDN5 and ICAM1 without decreasing the levels of ABCD1 protein itself. Together, these data demonstrate that ABCD1 deficiency induces significant alterations in brain endothelium via c-MYC and may thereby contribute to the increased trafficking of leucocytes across the blood–brain barrier as seen in cerebral adrenouleukodystrophy.